2004
DOI: 10.1002/anie.200352764
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Polymerization of 2,6‐Dimethylphenol To Form Poly(2,6‐dimethyl‐1,4‐phenyleneoxide) in Water

Abstract: Green polymerization: The simple stirring of 2,6‐dimethylphenol with an excess of oxidant or a catalytic amount of a copper complex in an alkaline aqueous solution yields poly(2,6‐dimethyl‐1,4‐phenyleneoxide), a commercially important polymer (see scheme). The formed polymer was easily separated as an off‐white powder by filtration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…As expected, both complexes can catalyze efficiently this polymerization with high activities and selectivities, viz., the selectivity to PPE is almost 90% for the two complexes, and the conversion of DMP is 85% for 1 and 90% for 2, which can match the reported well-known catalysts [32][33][34][35][36]. The origin of the interesting reactivities of complexes is thus discussed as well.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…As expected, both complexes can catalyze efficiently this polymerization with high activities and selectivities, viz., the selectivity to PPE is almost 90% for the two complexes, and the conversion of DMP is 85% for 1 and 90% for 2, which can match the reported well-known catalysts [32][33][34][35][36]. The origin of the interesting reactivities of complexes is thus discussed as well.…”
Section: Introductionsupporting
confidence: 64%
“…It has been demonstrated that the oxidation reaction of DMP did not proceed in the presence of Cu II catalyst alone, but was promoted significantly by adding base such as NaOMe in the reaction mixture [32]. The added base was found to have the role of generating the corresponding phenolate anion by dissociating the DMP molecule, which was critical in the whole catalytic process [38].…”
Section: Catalytic Properties Of Complexesmentioning
confidence: 99%
“…[36][37][38] To the best of our knowledge, PPO has never been exploited for the synthesis of fully aromatic di-or triblock copolymers, and a systematic study on the synthesis and functionalization of such block copolymers has not yet been done. Thus, we identified mono-phenol-terminated PPO oligomers as ideal candidates for use as aromatic block chains, and our work builds upon that of researchers [39][40][41] who reported the synthesis of PPO derivatives with low molecular weights.…”
Section: Introductionmentioning
confidence: 84%
“…Acetonitrile was suggested as the reaction medium in combination with the ligand 1,2-dimethylimidazole [60]. More recently, Saito et al succeeded in oxidatively polymerizing DMP to form PPO in water in the presence of a copper catalyst, base (NaOH) and dioxygen [73].…”
Section: Page 11 Of 96mentioning
confidence: 99%